The Relationship between Neovascular Age-Related Macular Degeneration and Erectile Dysfunction - Harun Çakmak; Tolga Kocatürk; Sema Oruç Dündar; Mehmet Dündar; Müjdat Karabulut (Journal of Ophthalmology)
Purpose. To evaluate association between erectile dysfunction (ED) and neovascular age-related macular degeneration (AMD). Methods. 195 men enrolled in this cross-sectional study. 90 of them had neovascular AMD and 105 of them were healthy volunteers. The International Index of Erectile Function (IIEF) questionnaire’s erectile function (EF) domain was used to assess ED. The patients in the study and control groups were statistically compared according to visual acuity, EF score, and body mass index. Results. The mean ages were 62 (54.5–73) and 60 (54–68), in the neovascular AMD and control groups, respectively. The total EF scores were 9 (6–16) in neovascular AMD and 18 (9.5–27) in control group. The results of IIEF questionnaire on neovascular AMD patients revealed that 85 men (94.4%) had some degree of ED, whereas 68 men (64.8%) had some degree of ED on control group. Patients with neovascular AMD had a significantly higher incidence of ED than control patients (). There was a significant association between ED and neovascular AMD (). Conclusions. Our results suggested that neovascular AMD has a high association with ED.